2016
DOI: 10.1161/jaha.116.003603
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiac Magnetic Resonance for Short‐Term Follow‐Up in Acute Myocarditis

Abstract: BackgroundCardiac magnetic resonance (CMR) can detect inflammatory myocardial alterations in patients suspected of having acute myocarditis. There is limited information regarding the degree of normalization of CMR parameters during the course of the disease and the time window during which quantitative CMR should be most reasonably implemented for diagnostic work‐up.Methods and ResultsTwenty‐four patients with suspected acute myocarditis and 45 control subjects underwent CMR. Initial CMR was performed 2.6±1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 35 publications
8
87
1
4
Order By: Relevance
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…1. A total of ten studies were included for the HCM group, 17,29-37 nine for DCM, 11,30,33,35,[38][39][40][41][42] twelve in MC, 30,[43][44][45][46][47][48][49][50][51][52][53] five in iron overload, 54-58 six in amyloidosis, 32,[59][60][61][62][63] two in Fabry disease, 64,65 ten in HT, 13,17,34,37,[66][67][68][69][70][71] four in DM, [72][73][74][75] and one in obesity 74 ( Table 1). The field strength is known to influence the T 1 values significantly 65 ; therefore, results from studies performed on a 1.5T or 3T are shown separately, but used as covariant in the meta-regression analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…The T 1 value for the whole SAX showed no significant difference between DCM patients and controls ( P = 0.05), while the T 1 values in the septal ROI were significantly increased for DCM patients ( P < 0.05). In addition to this, the T 1 values of studies that used the segmental approach also suffered from averaging . Furthermore, some studies used the 4‐chamber plane for T 1 mapping, which can lead to errors due to through‐plane respiratory motion.…”
Section: Discussionmentioning
confidence: 99%
“…Barone-Rochette et al (2014) also applied a simplified visual quantitative score of LGE to identify the outcomes of AM patients, with LGE identified as an independent predictor of all cause and cardiac mortality in these AM patients. In patients with AM, significantly continuous decrease of LGE volume percentage had been observed over several follow-up CMR examinations, which demonstrated a rapid and continuous decrease of myocardial inflammation (Luetkens et al, 2016). The myocardial inflammation was easier to subside in a small area of LGE, which indicated better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this question, Luetkens et al [52] reported that there was a significant and consistent decrease in all inflammatory CMR parameters over the course of the disease (p<0.01 for all parameters). Myocardial T1 and T2 relaxation times-indicative of myocardial edema-were the only single parameters showing significant differences between myocarditis patients and control subjects at the 5.5±1.3-week follow-up (native T1: 986.5±44.4 vs. 965.1± www.e-cvia.org 201 [53] reported that although both T2 and T1 mapping reliably detected acute myocarditis, only T2 mapping discriminated between acute and healed stages, underlining the incremental value of T2 mapping.…”
Section: Acute and Chronic Myocarditismentioning
confidence: 98%